The Effects of Ownership Structures on Firm Information Asymmetry in Malaysia - Yau, Josephine Tan Hwang; Goe, Zhen Qi; Rosita, Binti. Hamdan; Audrey, Liwan; Kueh, Jerome Swee Hui; Mohd Waliuddin, Bin Mohd Razali; Muhammad Asraf, Bin Abdullah (Human Resource Management Academic Research Society (HRMARS), 2019)
This paper presents the relationship between different types of blockholders with information asymmetry in Malaysian firms. To be more specific, this study divides the ownership structures into managerial blockholder, institutional blockholder and individual blockholder and ownership concentration while holding firm size and trading volume as control variables. On the other hand, the stock volatility and bid-ask spread are used as a proxy for information asymmetry. A sample of the top 150 largest public listed firms in term of market capitalisation is chosen from Bursa Malaysia from 2011 to 2015. Panel regression analysis is used to examine the data. The results show managerial blockholders, firm size and trading volume significantly influence information asymmetry. While institutional blockholders, individual blockholders and ownership concentration exhibit no relationship with information asymmetry. The study from this result can be useful for investors and the policymakers in Malaysia as it gives a clearer picture and more understandings on ownership structures and information asymmetry in the Malaysia market.